Pengecaman dan pencirian kulat polyporaceae dari hutan Sarawak yang berpotensi untuk penguraian lignin - Noreha, binti Mahidi (Universiti Malaysia Sarawak (UNIMAS), 2011)
Polyporaceae is among a group of potential fungi for biodegradaation and biocontrol which is commonly found on decaying woods on the forest floor. Considering the potentials of these fungi, research to document the occurrences and their potential as lignin degrader of Polyporaceae fungi in the study area was conducted. A total of 272 types of Polyporaceae were collected based on the occurrence of pores at the hymenium of fruiting body. As a result of detail observation in identification sample, 17 genera which included Ganoderma, Microporus, Fomes, Fomitopsis, Daedalea, Hexagonia, Rigidoporus, Irpex, Phellinus, Polyporus and Poria were identified.